The effect of the Oral Health Programme (bGEMS) on the oral health knowledge and attitudes of trainee teachers in Malaysia - Munirah Paiizi; Nor Faezah Md Bohari; Nawwal Alwani Mohd Radzi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: The Oral Health Programme for Trainee Teachers (bGEMS) is an annual collaborative program between the Malaysian Ministry of Health and the Ministry of Education. It was established in 1991 to enhance the oral health awareness of trainee teachers at the Institutes of Teacher Education (ITE). Despite being operational for over 30 years, limited evidence is available documenting the impact of bGEMS on trainee teachers’ oral health knowledge and attitudes, which may contribute to improving schoolchildren’s oral health. Purpose: This study aimed to assess the effectiveness of bGEMS by comparing oral health knowledge and attitudes between bGEMS participants and non-participants. Methods: This study employed a quasi-experimental design, with trainee teachers assigned to either the intervention (121 trainees) or control (119 trainees) groups. Data were collected using a validated questionnaire comprising 20 knowledge items and 10 attitude items. The data were analyzed using independent t-tests, paired t-tests, and simple linear regression. Results: The findings revealed that the intervention group showed significant improvements in oral health knowledge (0.70 ± 2.50, p=0.002) and attitudes (0.09 ± 0.31, p=0.002) following bGEMS. Conclusion: The findings revealed that the intervention group showed significant improvements in oral health knowledge (0.70 ± 2.50, p=0.002) and attitudes (0.09 ± 0.31, p=0.002) following bGEMS.